Designing Wireless Powered Networks Assisted by Intelligent Reflecting Surfaces With Mechanical Tilt - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Gacanin, Haris (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this letter, we propose a fairness-aware rate maximization scheme for a wireless powered communications network (WPCN) assisted by an intelligent reflecting surface (IRS). The proposed scheme combines user scheduling based on time division multiple access (TDMA) and (mechanical) angular displacement of the IRS. Each energy harvesting user (EHU) has dedicated time slots with optimized durations for energy harvesting and information transmission whereas, the phase matrix of the IRS is adjusted to focus its beam to a particular EHU. The proposed scheme exploits the fundamental dependence of the IRS channel path-loss on the angle between the IRS and the node’s line-of-sight, which is often overlooked in the literature. Additionally, the network design can be optimized for large number of IRS unit cells, which is not the case with the computationally intensive state-of-the-art schemes. In fact, the EHUs can achieve significant rates at practical distances of several tens of meters to the base station (BS) only if the number of IRS unit cells is at least a few thousand.
Keywords: Wireless power transfer; intelligent reflecting surfaces